The Effect of Course Review Horay (CRH) Cooperative Learning Model on Learning Outcomes of Elementary School Students - Mardiana (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to determine the effect of the CRH type of cooperative learning model on learning outcomes in the science subject on the water cycle material for fifth grade students at SD Negeri 34 Parepare. This study uses a quantitative approach with experimental research types and uses a Quasy Experimental design in the form of The Nonequivalent Pretest-Posttest Control Group Design. The sampling technique used in this study was saturated sampling with a total sample of 50 students. The data collection technique used in this study was a test in the form of multiple choice and documentation. Data analysis used descriptive statistical analysis techniques and inferential statistical analysis techniques. Based on the statistical results, it can be concluded that the CRH type cooperative learning model has an effect on learning outcomes in natural science students on the water cycle material for fifth grade students at SD Negeri 34 Parepare. The research recommendation is that subjects focus on other subjects.